A reconstruction of Proto-Tangkhulic rhymes - Mortensen, David R. (2024)
This paper presents a reconstruction of the rhyme system of Proto- Tangkhulic, the putative ancestor of the Tangkhulic languages, a Tibeto-Burman subgroup. A reconstructed rhyme inventory for the proto-language is presented. Correspondence sets for each of the members of the inventory are then systematically presented, along with supporting cognate sets drawn from four Tangkhulic languages: Ukhrul, Huishu, Kachai, and Tusom. This paper also summarizes the major sound changes that relate Proto-Tangkhulic to the daughter languages on which the reconstruction is based. It is concluded that Proto- Tangkhulic was considerably more conservative than any of these languages. It preserved the Proto-Tibeto-Burman length distinction in certain contexts and reflexes of final *-l, even though these are not preserved as such in Ukhrul, Huishu, Kachai, or Tusom. Proto-Tangkhulic is argued to be a potentially useful source of evidence in the reconstruction of Proto-Tibeto-Burman.